Achieving a 20% energy share from renewable sources: policies and legal rules for Poland. Issue 3 (December 2016) - Przybylska-Cząstkiewicz, Monika
Abstract : Poland is obligated to implement the law of the EU, established primarily in EU directives. With regard to the law on the renewable energy, Poland did not fulfil its duties in a timely manner, as it had not implemented Renewable Energy Directive (2009/28/EC) within the period specified in art. 27 of the said Directive, i.e. before 5 December 2010. As a consequence, Poland received a statement of objections regarding the failure to comply with the EU law, which objections were withdrawn as late as in February 2015 as a result of the legislative works on adopting the national act implementing Directive 2009/28/EC in relation to producing electric energy from renewable sources. The "Renewable Energy Sources Act" of 20 February 2015 is a comprehensive legal act containing regulations which support the development of producing electric energy from renewable sources. It is exactly those regulations that will constitute the main object of the analysis presented in this publication. It will describe legal instruments (primarily those related to supporting the production of energy) thanks to which Poland is currently making efforts to comply with the EU obligation with regard to producing energy from renewable sources.